MAPSS an Intelligent Architecture for the Pedagogical Support: Experiment, Results & Discussion - Hrich, Najoua; Lazaar, Mohamed; Khaldi, Mohamed (International Journal of Emerging Technologies in Learning (iJET), 2019)
In this paper, the authors have experimented the MaPSS (Multiagent pedagogical support system) which is an adaptive architecture based on ontologies and multi-agent systems for the presentation of the pedagogical support in its principal tasks: assessment of the knowledge, analyze of results and adapt remediation. In previous works, the authors have designed an ontology to present the relationship between the test questions and the concepts to evaluate and between those concepts and their remedial activities contents. Also, they have presented the operation of each agent (IT or human) of the system and the principle of collaboration between them. The experience consists on the use of an implemented prototype of MaPSS to support learners of Moroccan qualified secondary school in the domain of algorithmic and programming, and the impact of its use on the improving cognitive decision making to adapt learning.